2017
DOI: 10.1080/17436753.2016.1264122
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of using CeO2as a surrogate material during the investigation of UO2thermal conductivity enhancement

Abstract: A possible substitution of UO 2 for research purposes is the cerium dioxide (CeO 2 ) owing to its chemical and physical properties. Neutronic properties are different and fission is absent in the case of CeO 2 ; however, similarities were studied recently to have a possibility to compare the neutronic influence of secondary additives into the matrix. This paper deals with increasing the thermal conductivity of UO 2 nuclear fuel on surrogate material (CeO 2 ); the main focus of the research is given on the sint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…The relative densities achieved were 72.2 % to 91.3 % when non-milled powder was used, and 81.4 % to 95.4 % when milled powder was used. Data for particle size and morphology of the powder (in particular whether the powder is lath-shaped) were not reported by Roleček et al [24]. Cold-press-and-sinter of Nd2O3 has been reported [25] using powder with an average grain size of 4 µm, achieving a relative density of 86-89 % but with cracking attributed to a hygroscopic reaction.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The relative densities achieved were 72.2 % to 91.3 % when non-milled powder was used, and 81.4 % to 95.4 % when milled powder was used. Data for particle size and morphology of the powder (in particular whether the powder is lath-shaped) were not reported by Roleček et al [24]. Cold-press-and-sinter of Nd2O3 has been reported [25] using powder with an average grain size of 4 µm, achieving a relative density of 86-89 % but with cracking attributed to a hygroscopic reaction.…”
Section: Introductionmentioning
confidence: 95%
“…Wang [19] demonstrated the cold-press-and-sinter of CeO2 at a larger powder size of 5 µm; however, this was ball-milled before sintering. Roleček et al [24] reported a comparison of cold-press-and-sintered milled and non-milled powder. The relative densities achieved were 72.2 % to 91.3 % when non-milled powder was used, and 81.4 % to 95.4 % when milled powder was used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Traditional UO 2 fuel has the advantages of high melting point, outstanding radiation performance and exceptional compatibility with cladding materials, but it has the disadvantage of low thermal conductivity. 2,5 In the context of the Fukushima nuclear accident, the research on the accident-tolerant fuel system (ATF) has attracted the interests of many researchers. 6,7 Replacing UO 2 with new nuclear material is one of the focuses for the ATF development and ensures that the new fuel has high thermal conductivity and other advantageous properties.…”
Section: Introductionmentioning
confidence: 99%
“…visto que o óxido de cério é estruturalmente similar ao óxido de urânio: ambos são isoestruturais, i.e. possuem mesma estrutura fluorita, e com parâmetros de rede [62,70] tais que a CeO 2 a U O 2 = 5,40972 5,47127 ≈ 0,9888, sendo o CeO 2 frequentemente utilizado como substituto do UO 2 para fins de simulação de propriedades de pastilhas combustíveis [71,72,73,74] . Utilizando no refinamento Rietveld uma estrutura, denominada aqui de ρ, derivada de uma fase romboédrica observada para o sistema U-La-O, [75,68,76] Incidentalmente, utilizando a função do parâmetro de rede médio para o Figura 6.17 -Algumas regiões em detalhes do refinamento do padrão de difração da pastilha com 9,8 wt% de Er 2 O 3 , com os picos mais intensos de cada uma das fases α, β e ρ indicado.…”
Section: Possíveis Causas Da Separação De Fases Observada Nas Pastilhunclassified